A Simple High-Throughput Procedure for Microscale Extraction of Bioactive Compounds from the Flowers of Saint John’s Wort (Hypericum perforatum L.) - Mila Rusanova; Krasimir Rusanov; Marina Alekova; Liliya Georgieva; Pavlina Georgieva; Tzvetelina Zagorcheva; Ivan Atanassov (Applied Sciences)
We report the development of a procedure for ultrasound-assisted microscale extraction of metabolites from the flowers of Saint John’s wort (Hypericum perforatum L.), designed for comparative metabolite analysis of plants from genetic resource collections and natural and segregating populations. The procedure involves high-throughput methanol extraction of metabolites from ground-frozen flowers at a selected stage of flower development, which is carried out in a standard 2 mL Eppendorf tube. A total of 18 compounds, including chlorogenic acid, catechins, glycosylated flavonoids, hypericins, and hyperforin, were identified based on LC/DAD/QTOF analysis, of which 16 could be detected in the UV-Vis spectrum. Two alternative versions of the procedure were evaluated: the “single-flower” procedure, including repeated collection and analysis of single flowers from the tested plant, and the “bulk-flower” procedure, employing the collection of a bulk flower sample from the tested plant and analysis of a portion of the ground sample. The results showed excellent technical reproducibility of the “single-flower” procedure when used with the suggested combination of the peak areas for the proto- and stable forms of pseudohypericin and hypericin. Application of the developed “single-flower” procedure for comparison of the plants derived from seed progeny of the apomictic line Hp93 revealed significantly lower metabolite variation among the apomictic progeny plants compared to the variation observed among plants belonging to different genotypes.